An Anti-Tumor Vaccine Against Marek's Disease Virus Induces Differential Activation and Memory Response of γδ T Cells and CD8 T Cells in Chickens - Hao, Xiaoli; Li, Shuai; Li, Jiaqi; Yang, Yi; Qin, Aijian; Shang, Shaobin (Frontiers in Immunology, 2021)
Marek’s disease virus (MDV) is a highly oncogenic alphaherpesvirus that causes deadly T-cell lymphomas and serves as a natural virus-induced tumor model in chickens. The most efficacious vaccine, CVI988/Rispens (CVI988), against MD has been used for several decades. However, the mechanisms leading to protective immunity following vaccination are not fully understood. In this study, employing multi-parameter flow cytometry, we performed a comprehensive analysis of T cell responses in CVI988-vaccinated chickens. CVI988 vaccination induced significant expansion of γδ T cells and CD8α+ T cells but not CD4+ T cells in spleen, lung and blood at early time-points. The expansion of these cells was CVI988-specific as infection with very virulent MDV RB1B did not elicit expansion of either γδ or CD8α+ T cells. Phenotypic analysis showed that CVI988 vaccination elicited preferential proliferation of CD8α+ γδ T cells and CD8αα co-receptor expression was upregulated on γδ T cells and CD8α+ T cells after immunization. Additionally, cell sorting and quantitative RT-PCR showed that CVI988 vaccination activated γδ T cells and CD8α+ T cells which exhibited differential expression of cytotoxic and T cell-related cytokines. Lastly, secondary immunization with CVI988 induced the expansion of CD8+ T cells but not γδ T cells at higher magnitude, compared to primary immunization, suggesting CVI988 did induce memory CD8+ T cells but not γδ T cells in chickens. Our results, for the first time, reveal a potential role of γδ T cells in CVI988-induced immune protection and provide new insights into the mechanism of immune protection against oncogenic MDV.